Implementation of Laws Number 8 of 2016 Concerning Disabilities Persons in Bandar Lampung City in 2022 - Maya Zulvi Astarida; Zainudin Hasan (Universitas PGRI Madiun, 2021)
Philosophical and constitutional based on Pancasila and UUD 1945, each citizen had equal work opportunities, access public facilities, acquire a decent life, including those with disabilities. Law number 8 year 2016 on disabilities person emphasizes that